Prevention and Therapeutic Effects and Mechanisms of Tanshinone IIA Sodium Sulfonate on Acute Liver Injury Mice Model. (4th May 2016) - Lu, Lunjie; Zhou, Jun; Zhang, Jingying; Che, Jun; Jiao, Yang; Zhang, Yusong
Abstract : Tanshinone IIA sodium sulfonate (TSS) is a water-soluble derivative of tanshinone IIA, which is the main pharmacologically active component of Salvia miltiorrhiza. This study aimed to verify the preventive and therapeutic effects of TSS and its combined therapeutic effects with magnesium isoglycyrrhizinate (MI) in D-galactosamine- (D-Gal-) induced acute liver injury (ALI) in mice. The potential regulatory mechanisms of TSS on ALI were also examined. Our results may provide a basis for the development of novel therapeutics for ALI.